WACANA KESETIAAN DAN CINTA KASIH DALAM GLR ANALISIS SEMIOTIK - Septiani, Ni Kadek (Humanis; Volume 1. No. 1. November 2012, 2016)
Geguritan Luh Raras has a quirk in the convention padalingsa geguritan and build structures . GLR is unique because it uses only one pupuh, and pupuh ginada use to make geguritan story . These theories using a combination of several expert opinions such literary theory of the structure of Teeuw , Ratna , Endraswara , while the semiotic theory of Pierce , Lechte , Pradopo , Van Zoest and several other literary experts . To that end , an analysis of the literature GLR can be well Understood . This research was conducted several stages , namely : (1) providing phase the data using the method of reading , and assisted with technical translations ( literal and idiomatic ) and recording , (2) the stage of data analysis using descriptive analytic methods , and (3) the presentation stage analysis by applying formal methods and informal methods . The results obtained in this study is unfolding in the GLR semiotic study include Rich Parisudha Tri Philosophical teachings and Philosophical meaning of loyalty and love Luh Raras in the GLR .
Keywords: Semiotics , Discourse , Loyalty